0.9(6x+12)=1.6-(x+2)

Simple and best practice solution for 0.9(6x+12)=1.6-(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9(6x+12)=1.6-(x+2) equation:


Simplifying
0.9(6x + 12) = 1.6 + -1(x + 2)

Reorder the terms:
0.9(12 + 6x) = 1.6 + -1(x + 2)
(12 * 0.9 + 6x * 0.9) = 1.6 + -1(x + 2)
(10.8 + 5.4x) = 1.6 + -1(x + 2)

Reorder the terms:
10.8 + 5.4x = 1.6 + -1(2 + x)
10.8 + 5.4x = 1.6 + (2 * -1 + x * -1)
10.8 + 5.4x = 1.6 + (-2 + -1x)

Combine like terms: 1.6 + -2 = -0.4
10.8 + 5.4x = -0.4 + -1x

Solving
10.8 + 5.4x = -0.4 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
10.8 + 5.4x + x = -0.4 + -1x + x

Combine like terms: 5.4x + x = 6.4x
10.8 + 6.4x = -0.4 + -1x + x

Combine like terms: -1x + x = 0
10.8 + 6.4x = -0.4 + 0
10.8 + 6.4x = -0.4

Add '-10.8' to each side of the equation.
10.8 + -10.8 + 6.4x = -0.4 + -10.8

Combine like terms: 10.8 + -10.8 = 0.0
0.0 + 6.4x = -0.4 + -10.8
6.4x = -0.4 + -10.8

Combine like terms: -0.4 + -10.8 = -11.2
6.4x = -11.2

Divide each side by '6.4'.
x = -1.75

Simplifying
x = -1.75

See similar equations:

| 4n+3n=21 | | 2d+7+3d=-41 | | 2.5y+8= | | 2x+8=38+5x | | 4+2a=3(s-2)+1 | | 1.9(g-9.1)=-7.22 | | .5j=5 | | 11.54-d=6.54 | | 15.8=1.2(r-4)+9.8 | | 8x^2=4-7x | | 6=-4-2 | | 6+6x(x+8)= | | 5(9-11)=m-8 | | 2y=2y+40 | | -k+3=-4 | | 8m=-64 | | 4y+40=10y-20 | | U^2=15u+36 | | 21-42=3(x-2)-6 | | -2+8+n=-7+9 | | 2y-4x=8forx | | -2+8=-7+9 | | 10c^2-8c= | | 4x+20=48 | | 425-c=152 | | -15(z-899)=-930 | | 6a-42=2a-a | | -16+3+m=-7+17 | | -13(j-968)+125=385 | | -z/12=5 | | 4w^2-5=9w | | 4m+5(m+2)=1 |

Equations solver categories